Comparison between palm oil derivative and commercial thermo-plastic binder system on the properties of the stainless steel 316L sintered parts - Ibrahim, R.; Azmirruddin, M.; Wei, G. C.; Fong, L. K.; Abdullah, N. I.; Omar, K.; Muhamad, M.; Muhamad, S. (American Institute of Physics, 2010)
Link to publisher's homepage at http://scitation.aip.org/